Breast Imaging in Women Previously Irradiated for Hodgkin Lymphoma. (April 2016) - Horst, Kathleen C.; Fero, Katherine E.; Hancock, Steven L.; Advani, Ranjana H.; Ikeda, Debra M.; Daniel, Bruce; Rosenberg, Saul A.; Donaldson, Sarah S.; Hoppe, Richard T.
Abstract : Background: Women treated with mantle irradiation for Hodgkin lymphoma (HL) are at an increased risk of developing breast cancer (BC). Current guidelines recommend screening breast magnetic resonance imaging (MRI) as an adjunct to mammography (M) in these patients. There are limited data, however, as to the impact of breast MRI on cancer detection rates. The aim of the current study is to evaluate the use of breast MRI in survivors of HL treated and followed at a single institution. Materials and Methods: We retrospectively reviewed 980 female patients treated with mantle irradiation for HL between 1961 and 2008. Records were reviewed to determine age at radiotherapy treatment, radiotherapy dose, breast imaging (including M and breast MRI), biopsy results if applicable, and incidence of BC. Results: A total of 118 patients had breast imaging performed at our institution. Median age at HL diagnosis was 28 years (range, 10 to 69 y). Median radiotherapy dose was 36 Gy (range, 20 to 45 Gy). Seventy-nine patients (67%) underwent M screening only, 1 (1%) breast MRI only, and 38 (32%) both M and breast MRI. Of these 38, 19 (50%) underwent 54 screening MRI studies (range per patient=1 to 8), 13 (34%) underwent preoperative MRI for workup of BC, and 6 (16%) initiated screening MRI of the contralateral breast only after diagnosed with BC. Fifty-nine biopsies were performed: 47 were prompted by suspicious M findings only, 10 by palpable findings on physical examination (PE), and 2 by suspicious breast MRI findings. Of the 47 biopsies prompted by M, 24 revealed malignant disease, whereas 23 proved to be benign. All 10 biopsies performed by palpation were malignant. Both biopsies prompted by MRI findings were benign. With M, there were 34 true-positive findings in 32 patients, 23 false-positive findings, and 1 false-negative finding. With screening MRI, there were 2 false-positive findings, 1 false-negative finding, and no true-positive findings. Conclusions: The role of screening breast MRI in women previously irradiated for HL is evolving. Further education of patients and physicians is important to increase awareness of more sensitive BC screening modalities in this high-risk population. Future studies are necessary to determine the appropriate integration of screening breast MRI into the ongoing follow-up of these women.